"The situation is hopeless; we must take the next step": Reflecting on social action by academics in asylum seeker policy debate - Hartley, Lisa; Pedersen, A.; Fleay, Caroline; Hoffman, S. (The College of Community Psychologists of the Australian Psychological Society, 2013)
In this article, we reflect on the involvement of academics in the asylum seeker rights movement in Australia by documenting a collective action that was driven by the authors of this paper. This action was an open letter signed by 204 academics from a range of disciplines which voiced opposition to a number asylum seeker policies proposed by the two major political parties in mid-2012. Despite the noteworthy number of academic signatories to the letter, the question of whether academics have the responsibility to voice their concerns about social injustices remains a contentious issue. This is particularly so within mainstream psychology. In the first part of this paper, we draw on the foundations of community psychology to argue that academics that bear witness to the negative impact of asylum seeker policy have an ethical responsibility to engage in social actions outside of academia in response to what they witness. We also argue that this responsibility should be coupled with a reflection on the impacts of such social action. As such, in the second part of this paper, we critically reflect on the outcomes of the open letter action as part of bearing witness and consider why members of the asylum seeker rights movement keep going on in the face of very challenging political circumstances.